Discovery of ferroptosis-related genes in renal ischemia reperfusion and evaluate the potential impact on kidney transplantation - Zhou, Yao; Yang, Yuwei; Wang, Bo; Chen, Wan; Wei, Yanlin; Wu, Ruihua; Meng, LingZhang; Lyu, Liwen (Frontiers in Immunology, 2024)
Renal ischemia reperfusion injury (IRI) is one of the pivotal event of acute kidney injury (AKI), and they are unavoidable in the process of kidney transplantation, which eventually leads to the loss of renal allograft. Ferroptosis is a newly identified programmed cell death. Recent studies have suggested that ferroptosis may participate in the pathophysiological process of renal IRI.Therefore, we aimed to determine biomarkers associated with ferroptosis during renal IRI and their impact on renal allografts. In this study, we identified 60 ferroptosis-related genes (FRGs) in renal IRI based on the GSE148420 dataset and FerrDb database. And then we performed functional annotation analysis using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. Protein-protein interaction (PPI) network was constructed by online tool String. EZH2, CDKN1A, PPARA, EGR1, ATF3, and CD44 were identited as six ferroptosis-related hubgenes (FRHGs) using four methods, including MMC, Degree, DMNC, and EPC. FRHGs expression level were verified by the validation sets GSE58438 and GSE126805. Protein expression level of FRHGs verified by Proteomics and Western blot. Cibersort was utilized to analyze immune cell infiltration during renal IRI as well as the correlation between FRHGs and immune cells. The GSE21374 dataset was used for renal allografts survival analysis. Finally, We induced the IRI-AKI animal model and illustrated the importance of FRGHs CD44 in ferroptosis. Through comprehensive analysis of gene expression and animal experiment, this study provided new insights into the pathogenesis of renal IRI and provided new evidence for its diagnosis or treatment.